Bessel Beam Coherent Anti-Stokes Raman Scattering Spectroscopy for Turbulent Flow Diagnosis. Issue 3 (March 2023) - Li, Runfeng; Lan, Ruijun; Dong, Dashan; Yang, Hong; Shi, Kebin
Coherent anti-Stokes Raman scattering (CARS) spectroscopy plays an important role in chemical analysis for transient flow dynamics. Due to the turbulent ambient conditions, the CARS spectrum often suffers from a poor signal-to-noise ratio (SNR) and cannot provide a convincing measurement. Here, we report on a CARS spectroscopic method using a Bessel beam to enhance the spectral fidelity and SNR in a quasi-turbulent environment. Compared with traditional CARS, the measurement accuracy is significantly improved by taking advantage of the anti-scattering and self-healing characteristics of the Bessel beam. Our preliminary results indicate that Bessel beam CARS could be a promising method for high precision turbulent flow measurement fields. Graphical Abstract